Rapid identification of novel functional promoters for gene therapy - Pringle, I; Gill, D; Connolly, M; Lawton, A; Hewitt, A; Nunez-Alonso, G; Davies, L; Hyde, S; Cheng, S; Scheule, R (2012)
Transcriptional control of transgene expression is crucial to successful gene therapy, yet few promoter/enhancer combinations have been tested in clinical trials. We created a simple, desktop computer database and populated it with promoter sequences from publicly available sources. From this database, we rapidly identified novel CpG-free promoter sequences suitable for use in non-inflammatory, non-viral in vivo gene transfer. In a simple model of lung gene transfer, five of the six promoter elements selected, chosen without prior knowledge of their transcriptional activities, directed significant transgene expression. Each of the five novel promoters directed transgene expression for at least 14 days post-delivery, greatly exceeding the duration achieved with the commonly used CpG-rich viral enhancer/promoters. Novel promoter activity was also evaluated in a more clinically relevant model of aerosol-mediated lung gene transfer and in the liver following delivery via high-pressure tail vein injection. In each case, the novel CpG-free promoters exhibited higher and/or more sustained transgene expression than commonly used CpG-rich enhancer/promoter sequences. This study demonstrates that novel CpG-free promoters can be readily identified and that they can direct significant levels of transgene expression. Furthermore, the database search criteria can be quickly adjusted to identify other novel promoter elements for a variety of transgene expression applications. © 2012 Springer-Verlag.